Prenatal exposure to NaF alters dental eruption by decrease of osteoclast number in the molar bone crypt of rats - Interlandi, Victoria (2018)
Fil: Interlandi, Victoria. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Química Biológica A; Argentina.